2023
DOI: 10.21203/rs.3.rs-2585336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SP1/CTR1 mediated oxidative stress-induced cuproptosis in intervertebral disk degeneration

Abstract: Intervertebral disk degeneration (IDD) is the primary pathology responsible for lower back pain. Oxidative stress-induced cell death plays a fundamental role in IDD pathogenesis. Cuproptosis is a recently discovered form of programmed cell death dependent on copper availability. Whether cuproptosis is involved in IDD progression remains unknown. Herein, we established in vitro and in vivo models to investigate the presence of cuproptosis in IDD and the mechanisms by which oxidative stress interacts with copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…[8,9] Several studies have suggested that bioactive materials could attenuate IVDD by inhibiting cellular senescence without causing cell death. [10,11] Mitochondrial dysfunction and consequent redox imbalance are shared hallmarks of cellular senescence and IVDD, yet translational solutions to address these issues are limited. [12][13][14] Thus, developing more bioavailable senomorphics with mitochondrion-targeted or redox-modulating properties for IVDD treatment would be prudent.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Several studies have suggested that bioactive materials could attenuate IVDD by inhibiting cellular senescence without causing cell death. [10,11] Mitochondrial dysfunction and consequent redox imbalance are shared hallmarks of cellular senescence and IVDD, yet translational solutions to address these issues are limited. [12][13][14] Thus, developing more bioavailable senomorphics with mitochondrion-targeted or redox-modulating properties for IVDD treatment would be prudent.…”
Section: Introductionmentioning
confidence: 99%